Periprocedural Direct Oral Anticoagulant Management: The RA-ACOD Prospective, Multicenter Real-World Registry - Ferrandis, Raquel; Llau, Juan V.; Sanz, Javier F.; Cassinello, Concepción M.; González-Larrocha, Óscar; Matoses, Salomé M.; Suárez, Vanessa; Guilabert, Patricia; Torres, Luís-Miguel; Fernández-Bañuls, Esperanza; García-Cebrián, Consuelo; Sierra, Pilar; Barquero, Marta; Montón, Nuria; Martínez-Escribano, Cristina; Llácer, Manuel; Gómez-Luque, Aurelio; Martín, Julia; Hidalgo, Francisco; Yanes, Gabriel; Rodríguez, Rubén; Castaño, Beatriz; Duro, Elena; Tapia, Blanca; Pérez, Antoni; Villanueva, Ángeles M.; Álvarez, Juan-Carlos; Sabaté, Sergi; for the RA-ACOD investigators (TH Open, 2020)
Introduction There is scarce real-world experience regarding direct oral anticoagulants (DOACs) perioperative management. No study before has linked bridging therapy or DOAC-free time (pre-plus postoperative time without DOAC) with outcome. The aim of this study was to investigate real-world management and outcomes.Methods RA-ACOD is a prospective, observational, multicenter registry of adult patients on DOAC treatment requiring surgery. Primary outcomes were thrombotic and hemorrhagic complications. Follow-up was immediate postoperative (24–48 hours) and 30 days. Statistics were performed using a univariate and multivariate analysis. Data are presented as odds ratios (ORs [95% confidence interval]).Results From 26 Spanish hospitals, 901 patients were analyzed (53.5% major surgeries): 322 on apixaban, 304 on rivaroxaban, 267 on dabigatran, 8 on edoxaban. Fourteen (1.6%) patients suffered a thrombotic event, related to preoperative DOAC withdrawal (OR: 1.57 [1.03–2.4]) and DOAC-free time longer than 6 days (OR: 5.42 [1.18–26]). Minor bleeding events were described in 76 (8.4%) patients, with higher incidence for dabigatran (12.7%) versus other DOACs (6.6%). Major bleeding events occurred in 17 (1.9%) patients. Bridging therapy was used in 315 (35%) patients. It was associated with minor (OR: 2.57 [1.3–5.07]) and major (OR: 4.2 [1.4–12.3]) bleeding events, without decreasing thrombotic events.Conclusion This study offers real-world data on perioperative DOAC management and outcomes in a large prospective sample size to date with a high percentage of major surgery. Short-term preprocedural DOAC interruption depending on the drug, hemorrhagic risk, and renal function, without bridging therapy and a reduced DOAC-free time, seems the safest practice.
Keywords: anticoagulant; dabigatran etexilate; apixaban; rivaroxaban; perioperative period